UJI EFEKTIVITAS ANTIBIOTIK EKSTRAK DAUN CENGKEH (SYZYGIUM AROMATICUM) TERHADAP PERTUMBUHAN BAKTERI SALMONELLA TYPI SECARA IN VITRO - Ristiansyah, Dilla Ulfa; Yenita, Yenita; Melviana, Melviana; Annisa, Annisa (JURNAL IBNU SINA BIOMEDIKA, 2018)
Typhoid fever is an enteric bacterial infection caused by Salmonella enterica serovar Typhi or Paratyphi. Salmonella typhi is a Gram negative rod which has no spores and moves with flagel peritric. Salmonella is facultative intracellular and facultative anaerobes. Clove leaves (Syzygium aromaticum) have antibiotic effects on bacteria and known can inhibit Salmonella typhi bacteria. Methodology: This study used an experimental method. The technique used in measuring antibiotic activity is the method of disk diffusion. Result: The concentration of 10%, 15%, 20% and 25% clove leaf extracts resulted in average of 11.89 mm, 11.40 mm, 16.76 mm, and 16.90 mm respectively. while the clear zone diameter of chloramphenicol is 20.74 mm.Conclusion: Clove leaf extract at 25% concentration has high clear zone in treatment group. Keywords: Salmonella typhi, Clove Leaf extractKeywords : Salmonella typhi, Cengke leafâs extractÂ Â Â Â